P04.18 Heterogeneity and plasticity of integrin α5β1 expression in glioblastoma stem cells. (9th September 2021) - Messé, M; Bernhard, C; Mercier, M; Fuchs, Q; Foppolo, S; Herold-Mende, C; Namer, I; Bund, C; Elati, M; Entz-Werlé, N; Dontenwill, M
Abstract: BACKGROUND: Glioblastoma (GBM) is the most frequent and deadliest type of central nervous system tumors. Despite the treatment by the Stupp protocol, almost all patients relapse and new therapeutic protocols have been unsuccessful for ameliorating patient survival. Molecular heterogeneity of GBM and existence of glioma stem cells (GSC) may be linked to therapy resistance and recurrence. We demonstrated earlier that α5β1 integrin is a GBM therapeutic target which participate to therapy resistance; a high expression in patient tumors is linked to a worse prognosis. Expression of α5β1 integrin is heterogeneous inter- and intra-tumorally. We particularly addressed the role of glioma stem cell plasticity in the modulation of the integrin expression. Stem cells reside in specific niches (perivascular or hypoxic niches) in the tumor and are at the origin of the more differentiated tumor cell bulk. Metabolism is known to change between the different GSC states and may be affected by or may affect the integrin expression. The aim of our work is therefore to consider the expression of the integrin α5β1 in relationship with GSC differentiation or in hypoxic environment and with cell metabolism. MATERIAL AND METHODS: Ten different patient-derived glioma stem cell lines were investigated. Cell culture in stem cell medium (neurospheres) or differentiation medium (adherent cell monolayer) was made in normoxia (21% O2) or hypoxia (1%O2). Alternatively, chemically-induced hypoxia (cobalt chloride/desferoxiamine) was used. Integrin expression was kinetically checked at the mRNA (RT-qPCR) or protein (Western blot) levels. Cell metabolism was investigated with the Seahorse Xfp technology and by HRMAS-NMR. RESULTS: No GSC lines (neurospheres) expressed the α5β1 integrin. Interestingly, only half of them did after differentiation suggesting a first level of heterogeneity. A second level of heterogeneity was observed in hypoxic conditions provoking induction of integrin α5β1 expression in only some non-differentiated GSC. Three categories of GSC were thus characterized: one able to express the integrin in hypoxia and after differentiation, one never expressing it and the third one only after differentiation. Cell metabolism differed between GSC before and after differentiation and in presence of integrin α5β1 antagonists. Specific glioma regulator network analysis revealed new targets to be inhibited concomitantly with the integrin. CONCLUSION: Data suggest that α5β1 integrin expression may be induced by different signaling pathways. Molecular switches may occur either when stem cells differentiate to tumor cells but also directly in stem cells in hypoxic niches. Characterization of α5β1 integrin expression drivers may help to find new therapeutic targets but also to delineate subpopulation of patients who would benefit from an anti-integrin strategy.